Dinâmicas comunicacionais de (in) visibilidade na experiência de refugiadas/os e imigrantes LGBTIQ+ nas cidades de São Paulo e Barcelona - Theodoro, Hadriel Geovani da Silva (2021)
The main objective of the research is to analyze the communicational dynamics of (in)visibility in the experiences of LGBTIQ+ refugees and immigrants living in the cities of São Paulo (Brazil) and Barcelona (Spain). Theoretical contributions are transdisciplinary and come from studies in communication; consumption; visibility; migrations; gender and sexuality. The research has a qualitative character and counts on a multimetodological approach, developed along three main axes: a) literature review about the theories that support it; b) data survey, using participant observation techniques in collective and institutional spaces linked to the experiences of LGBTIQ+ refugees and immigrants in the cities of São Paulo and Barcelona, and the performance of semi-structured interviews – with advisors from the Municipalities of São Paulo and Barcelona, with a social worker from Missão Paz and with the director of the Associació Catalana per la Integració d'Homosexuals, Bisexuals i Transsexuals Immigrants (non-governmental institutions aimed at welcoming refugees and immigrants), and with 20 LGBTIQ+ refugees and immigrants (10 in each urban center); c) data processing and data analysis carried out from two spheres: socio-communicational networks and migratory journeys. In both urban centers, there is a structural invisibility of the theme, although it is more accentuated in the case of the city of São Paulo. This invisibility is reflected in the performance of governmental and non-governmental institutions with regard to the development and implementation of public policies or services aimed at LGBTIQ+ refugees and immigrants. Regarding the migratory journeys of the subjects interviewed , it was possible to verify that the communicational dynamics of (in)visibility are directly or indirectly implicated in their displacement experiences, encompassing processes of subjectification, the (de)construction of imaginaries, the adaptation to new contexts of residence, the appropriation of spaces (symbolic and physical) of the city, forms of political engagement and activism, the exercise of citizenship, the origin or continuity of situations of violence, and the vulnerability and/or precariousness of their existence.